Obstetrical specificities of Ivorian adolescent mothers on a single-center hospital series of 1040 cases - Edele Kacou Aka; Apollinaire Horo; Mohamed Fanny; Luc Olou; Perel Konan; Abdoul Koffi; Ana Toure-Ecra; Mamourou Kone (BMJ Publishing Group, 2022)
Overview and aim: The precocity of sexual intercourse among adolescent girls is a prominent source of unwanted pregnancy. Here, we aim to survey the past issues relating to the pregnancy, childbirth, and materno-fetal prognosis of Ivorian adolescent women. Methods: We conducted a retrospsective study with adolescent group (n ​= ​1040) versus young adult group aged 20 to 24 (n ​= ​736) over three years from1st January 2016 to 31rd December 2018 ​at the Department of Obstetrics and Gynecology at the University of Abidjan-Yopougon Hospital. Maternal and fetal outcomes of the two groups were analyzed and compared by using Pearson's Chi2 tests and Fisher's exact tests, followed by multivariate analysis and logistic regression using Stata software version 20. Results: The average age of adolescent girls in our study was 17.45 years (SD ​= ​1.39) and a minimum of 12 years. Adolescents consulted less (P ​< ​0.0001) and later (P ​< ​0.0001) versus young adults aged 20 to 24. The proportion of adolescent girls (47.6%) versus young adults (39.1%) who had underwent caesarean section was significantly higher (P ​= ​0.0004). These adolescents were 3.5-fold more likely to develop hypertension and its complications in the postpartum period and 2.5-fold more likely to contract a postpartum infection. Maternal mortality was not significantly associated with adolescence (OR ​= ​0.52 (95%CI: 0.22-1.19; P ​= ​0.0891). The risk of prematurity, early neonatal death, and neonatal admission were 2.02 (95%CI: 1.56-2.63; P ​< ​0.0001), 1.55 (95%CI: 1.14-2.13; P ​= ​0.0040), and 1.73 (95%CI:1.12-2.71; P ​= ​0.0097) in adolescence, respectively. Conclusion: Adolescent childbirth remains associated with a poor prognosis.